Advantages of confining the fountain in a conical spouted bed reactor for biomass steam gasification. (15th June 2018) - Cortazar, M.; Lopez, G.; Alvarez, J.; Amutio, M.; Bilbao, J.; Olazar, M.
Abstract: A study was carried out on the advantages of inserting a fountain confiner in conical spouted beds for biomass steam gasification and the results (gas yield and composition, tar content, carbon conversion efficiency and H2 production) are compared with those obtained under conventional spouting regime. The experiments were carried out in a bench scale unit operating in continuous regime under the same gasification conditions in all the configurations (850 °C, S/B ratio of 2 and olivine as primary catalyst). The gaseous product was analyzed by on-line gas chromatography and micro-gas chromatography, and the tars by gas chromatography-mass spectrometry. The use of a fountain confiner allows enhancing process versatility, increasing gas velocity over the minimum spouting one, increasing the fountain height and reducing olivine particle size (enhanced fountain regime). Thus, as a result of a better gas-solid contact, tar content was reduced from 49.2 g Nm −3 without fountain confiner to 20.6 g Nm −3 under enhanced fountain regime, with the reduction of heavy PAHs being especially remarkable. In the same line, a great improvement in process conversion efficiency was attained under the enhanced fountain regime, with gas production reaching a value of 1.3 m 3 kg −1 and that of H2 production 5.0 wt%. Highlights: Fountain confining increases gas residence time in the gasifier. Enhanced fountain regime promotes turbulence, heat transfer and gas-solid contact. Gasification performance was improved operating under enhanced fountain regime. Under the optimum conditions tar content was reduced by 59 wt% up to 20.6 g Nm −3 . Fountain confining selectively reduces the heavy PAH fraction in the tar.